Ultrathin flexible magnetic eyelash magnetic sheet and preparation method thereof
By using samarium-iron nitrogen magnetic powder and polypropylene composite materials to prepare ultra-thin flexible magnetic eyelash magnetic sheets, and using gradient distributed directional impulse technology, the existing magnetic eyelashes are solved, and the magnetic eyelashes with high safety and controllable magnetic force are achieved.
Patent Information
- Application Number
- CN202510253349.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-05
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2045-03-05
AI Technical Summary
The existing magnetic eyelashes have problems such as heavy, easy to break, easy to fall off, unnatural wearing effect, and poor corrosion resistance of the material.
Ultra-thin flexible magnetic eyelash magnetic sheets are prepared by using samarium-iron nitrogen magnetic powder and polypropylene composite materials, and the magnetization structure is formed through gradient distributed directional impulse, increasing corrosion resistance.
The preparation of ultra-thin flexible magnetic eyelash magnetic sheet is realized, overcoming the problems of easy falling off and heavy traditional magnetic eyelashes, improving wear comfort and biosafety, and having good corrosion resistance.
Smart Images

Figure CN119742140A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of magnetic eyelashes, and in particular to an ultra-thin flexible magnetic eyelash sheet and a preparation method thereof. Background Art
[0002] Traditional false eyelashes are composed of a connecting part and false eyelashes bonded to the connecting part, with adhesive coated on one side of the connecting part, and the connecting part is bonded to the eyelid when worn. Such traditional false eyelashes have many defects, such as high cost of use, irritation of the adhesive to human skin, and inconvenience in wearing and removing.
[0003] In order to overcome the above problems, people have developed magnetic false eyelashes, which can be worn by combining a sheet of eyelashes with magnetic elements with a magnetic eyeliner, or by magnetically adsorbing the upper and lower eyelashes from both sides of the real eyelashes. However, existing magnetic eyelashes also have some shortcomings. For example, when the magnetic element is a hard magnetic sheet, it is heavy and the strong magnetic attraction can easily damage the real eyelashes of the human eye; when the magnetic element is a flexible magnetic strip, the magnetic force is weak and it is easy to slip off, not fit the roots of the real eyelashes of the human eye, and other problems, which affect the wearing effect and comfort. Summary of the invention
[0004] The present invention proposes an ultra-thin flexible magnetic eyelash sheet and a preparation method thereof, which solves the problems in the related art that the magnetic eyelashes are thick, easy to break, easy to fall off, have an unnatural wearing effect, and have poor corrosion resistance.
[0005] The technical solution of the present invention is as follows: In the first aspect, the present invention proposes an ultra-thin flexible magnetic eyelash magnet sheet, each set of eyelash magnet sheets is composed of two upper and lower magnet sheets, and the two magnet sheets are respectively arranged with opposing magnetic poles, and the magnetism of the opposing magnetic poles is distributed on the magnet sheet in a gradient manner with strong edges and weak middle; The magnetic sheet comprises the following raw materials in parts by weight: 85-89 parts of samarium iron nitrogen magnetic powder and 11-15 parts of polypropylene; preferably, 87 parts of samarium iron nitrogen magnetic powder and 13 parts of polypropylene.
[0006] As a further solution of the present invention: the magnetic sheet further comprises the following raw materials: silane coupling agent, calcium stearate, zinc oxide; Wherein, the weight of the silane coupling agent is 1.5% of the samarium iron nitrogen magnetic powder; the weight of the calcium stearate is 0.3% of the polypropylene; and the weight of the zinc oxide is 0.3% of the polypropylene.
[0007] As a further solution of the present invention: the SmFeN magnetic powder is subjected to surface corrosion resistance treatment, and the surface corrosion resistance treatment method is: adding phosphoric acid and corrosion inhibitor to the SmFeN magnetic powder and stirring evenly to form a mixed system, and then reacting at 100°C for 6 hours.
[0008] As a further solution of the present invention: the amount of the phosphoric acid is 1 wt % of the mixed system, and the amount of the corrosion inhibitor is 1 wt % of the mixed system.
[0009] As a further solution of the present invention: the thickness of the magnetic sheet is 0.14-0.24 mm.
[0010] As a further solution of the present invention: the surface magnetic induction intensity of the magnetic sheet is 32-50mT.
[0011] As a further solution of the present invention: the surface magnetic induction intensity at the edge of the magnetic sheet is greater than the surface magnetic induction intensity at the center, and the surface magnetic induction intensity at the edge of the magnetic sheet is 38-50mT, and the surface magnetic induction intensity at the center of the magnetic sheet is 30-42mT.
[0012] Furthermore, the surface magnetic induction intensity from the center of the magnetic sheet to the edge of the magnetic sheet increases uniformly.
[0013] In a second aspect, the present invention further discloses a method for preparing the ultra-thin flexible magnetic eyelash magnet sheet as described above, comprising the following steps: Step 1: Mix the magnetic sheet raw materials according to proportion to obtain a mixed material; Step 2: putting the mixed materials into a twin-screw extruder, melt-blending and granulating at 180-210° C. to obtain pellets; Step 3: Place a layer of Teflon paper under the pressing fixture of the flat vulcanizer, then scatter the pellets, place another piece of Teflon paper on top of the pellets, and then press at 185°C. Control the pressing size to , pressing to a thickness of 0.14-0.24 mm to obtain a magnetic sheet precursor; Step 4: clean the burrs of the magnetic sheet precursor, cut it into two even sheets, stack them, and punch them into a single set of sheets using a sheet punching machine; Step 5: Perform gradient distributed directional magnetization on each group of sheets to form a counter-attractive magnetized structure.
[0014] As a further solution of the present invention: in step 5, the method of performing gradient distributed directional magnetic punching on each group of sheets includes the following steps: Step a: Place a single set of sheets between double layers of acrylic plates; Step b, placing the plate holding the sheet material horizontally and centered on the conveyor belt; Step c, pre-orienting the plate with a conveyor belt through a strong magnetic field of upper S and lower N, wherein the strong magnetic field includes two upper and lower N52 NdFeB strong magnetic blocks, and the magnetism of the two N52 NdFeB strong magnetic blocks is in a gradient distribution with strong edges and weak middle; a unidirectional magnetic field is formed in the middle; Step d, magnetizing by a pulsed magnetic field; Step e: After magnetization, the two magnetic sheets are reversed to realize a counter-attractive magnetization structure.
[0015] As a further solution of the present invention: in step d, the intensity of the pulsed magnetic field is 3.5 T, and the magnetization time is 200 ms.
[0016] The working principle and beneficial effects of the present invention are: 1. The ultra-thin flexible magnetic eyelash magnet sheet of the present invention adopts samarium iron nitrogen magnetic powder as the magnetic material and a composite material of polypropylene. The samarium iron nitrogen is non-toxic and resistant to sweat corrosion. The polypropylene meets the cosmetic grade standard, improves the biological safety, and solves the problem of unreliable materials of traditional magnetic eyelashes. The magnetic sheet is designed as a magnetized structure of mutual attraction. The upper and lower layers of magnetic sheets can achieve firm adsorption, which overcomes the disadvantage that traditional magnetic eyelashes are easy to fall off. 2. The ultra-thin flexible magnetic eyelash sheet of the present invention is pressed by flat vulcanization technology, with a thickness of only 0.14-0.24mm. It can be folded in half for more than 500 times without breaking, fits the curvature of the eye, is comfortable to wear, and avoids the defects of the traditional thick magnetic eyelashes; it breaks through the thickness limit of the traditional calendering process, is conducive to the preparation of ultra-thin magnetic sheets, and reduces production costs; 3. The ultra-thin and flexible magnetic eyelash magnet of the present invention can control the magnetic induction intensity on the surface of the magnet within the range of 32-50mT by adjusting the magnetic powder content, thereby achieving graded adsorption force, meeting the needs of different users for daily or thick styles, and providing diversified choices; and is designed as a gradient magnetization structure, which can achieve a balance between natural curling of eyelashes and firm adsorption, thereby obtaining ultra-thin and flexible, highly safe and controllable magnetic eyelashes. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] The present invention will be further described in detail below in conjunction with the accompanying drawings and specific embodiments.
[0018] Figure 1 It is a schematic diagram of placing a layer of Teflon paper under the pressing fixture of the flat vulcanizing machine in step 3 of embodiment 2 of the present invention; Figure 2 is a schematic diagram of a magnetic sheet precursor in step 3 of Example 2 of the present invention; Figure 3 Schematic diagram of the ultra-thin flexible magnetic eyelash magnet prepared in Example 2 of the present invention. DETAILED DESCRIPTION
[0019] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0020] The experimental methods in the following examples, unless otherwise specified, are all conventional methods, and are performed according to the techniques or conditions described in the literature in the field or according to the product instructions. The materials used in the following examples, unless otherwise specified, can all be obtained from commercial channels.
[0021] Example 1
[0022] Preparation of SmFeN magnetic powder: add phosphoric acid and TTA methylbenzotriazole to the SmFeN magnetic powder, stir evenly to form a mixed system, and then react at 100°C for 6 hours; wherein the amount of phosphoric acid is 1% of the mixed system, and the amount of corrosion inhibitor is 1% of the mixed system.
[0023] Example 2
[0024] The present embodiment provides an ultra-thin flexible magnetic eyelash magnet sheet, which is composed of samarium iron nitrogen magnetic powder, polypropylene resin, KH550 silane coupling agent, calcium stearate and zinc oxide raw materials; wherein the weight parts of the system formed by the samarium iron nitrogen magnetic powder and the polypropylene resin and the amounts of other raw materials are specifically as follows.
[0025] SmFeN magnetic powder (from Example 1, average particle size 2 μm, coercivity Hc ≥ 12 kOe): 87 wt%; Polypropylene (PP, melt index 20g / 10min): 13wt%; Silane coupling agent (KH-550): 1.5% of the mass of SmFeN magnetic powder; Calcium stearate: 0.3% of PP mass; Zinc oxide: 0.3% of PP mass.
[0026] The preparation process of the ultra-thin flexible magnetic eyelash magnet is as follows: Step 1: Mix the magnetic sheet raw materials according to proportion to obtain a mixed material; Step 2: putting the mixed materials into a twin-screw extruder, melt-blending and granulating at 200° C. to obtain pellets; Step 3: Figure 1-2 As shown, a layer of Teflon paper is placed under the pressing fixture of the flat vulcanizer, and then the pellets are dispersed and placed, and another piece of Teflon paper is placed on top of the pellets, and then pressed at 185°C, and the pressing size is controlled to be , pressing to a thickness of 0.14 mm to obtain a magnetic sheet precursor; Step 4: clean the burrs of the magnetic sheet precursor, cut it into two even sheets, stack them, and punch them into a single set of sheets using a sheet punching machine; Step 5, place a single set of sheets between double-layer acrylic plates; place the acrylic plates holding the sheets horizontally and centered on the conveyor belt; pre-orient the acrylic plates along the conveyor belt through a strong magnetic field of upper S and lower N, wherein the strong magnetic field includes two upper and lower N52 NdFeB strong magnetic blocks, and the magnetism of the two N52 NdFeB strong magnetic blocks is distributed in a gradient with strong edges and weak middle; a unidirectional magnetic field is formed in the middle; magnetization is performed for 200ms through a pulse magnetic field with an intensity of 3.5T; after magnetization, the two magnetic sheets are reversed to realize a magnetized structure of mutual attraction, and the following is obtained: Figure 3 The ultra-thin flexible magnetic eyelash magnet of the present embodiment is shown.
[0027] Example 3
[0028] The present embodiment provides an ultra-thin flexible magnetic eyelash magnet sheet, which is composed of samarium iron nitrogen magnetic powder, polypropylene resin, silane coupling agent, calcium stearate and zinc oxide raw materials; wherein the weight parts of the system formed by the samarium iron nitrogen magnetic powder and polypropylene resin and the amounts of other raw materials are specifically as follows.
[0029] SmFeN magnetic powder (from Example 1, average particle size 2 μm, coercivity Hc ≥ 12 kOe): 87 wt%; Polypropylene (PP, melt index 20g / 10min): 13wt%; Silane coupling agent (KH-550): 1.5% of the mass of SmFeN magnetic powder; Calcium stearate: 0.3% of PP mass; Zinc oxide: 0.3% of PP mass.
[0030] The preparation process of the ultra-thin flexible magnetic eyelash magnet is as follows: Step 1: Mix the magnetic sheet raw materials according to proportion to obtain a mixed material; Step 2: putting the mixed materials into a twin-screw extruder, melt-blending and granulating at 180° C. to obtain pellets; Step 3: Place a layer of Teflon paper under the pressing fixture of the flat vulcanizer, then scatter the pellets, place another piece of Teflon paper on top of the pellets, and then press at 185°C. Control the pressing size to , pressing to a thickness of 0.19 mm to obtain a magnetic sheet precursor; Step 4: clean the burrs of the magnetic sheet precursor, cut it into two even sheets, stack them, and punch them into a single set of sheets using a sheet punching machine; Step 5, place a single set of sheets between double-layer acrylic plates; place the acrylic plates holding the sheets horizontally and centered on the conveyor belt; pre-orient the acrylic plates along the conveyor belt through a strong magnetic field of upper S and lower N, wherein the strong magnetic field includes two upper and lower N52 NdFeB strong magnetic blocks, and the magnetism of the two N52 NdFeB strong magnetic blocks corresponds to a gradient distribution with strong edges and weak middle; a unidirectional magnetic field is formed in the middle; magnetization is performed for 200ms through a pulsed magnetic field with an intensity of 3.5T; after magnetization, the two magnetic sheets are reversed to realize a magnetized structure of mutual attraction, thereby obtaining the ultra-thin flexible magnetic eyelash magnetic sheet of this embodiment.
[0031] Example 4
[0032] The present embodiment provides an ultra-thin flexible magnetic eyelash magnet sheet, which is composed of samarium iron nitrogen magnetic powder, polypropylene resin, silane coupling agent, calcium stearate and zinc oxide raw materials; wherein the weight parts of the system formed by the samarium iron nitrogen magnetic powder and polypropylene resin and the amounts of other raw materials are specifically as follows.
[0033] SmFeN magnetic powder (from Example 1, average particle size 2 μm, coercivity Hc ≥ 12 kOe): 87 wt%; Polypropylene (PP, melt index 20g / 10min): 13wt%; Silane coupling agent (KH-550): 1.5% of the mass of SmFeN magnetic powder; Calcium stearate: 0.3% of PP mass; Zinc oxide: 0.3% of PP mass.
[0034] The preparation process of the ultra-thin flexible magnetic eyelash magnet is as follows: Step 1: Mix the magnetic sheet raw materials according to proportion to obtain a mixed material; Step 2: putting the mixed materials into a twin-screw extruder, melt-blending and granulating at 210° C. to obtain pellets; Step 3: Place a layer of Teflon paper under the pressing fixture of the flat vulcanizer, then scatter the pellets, place another piece of Teflon paper on top of the pellets, and then press at 185°C. Control the pressing size to , pressing to a thickness of 0.24 mm to obtain a magnetic sheet precursor; Step 4: clean the burrs of the magnetic sheet precursor, cut it into two even sheets, stack them, and punch them into a single set of sheets using a sheet punching machine; Step 5, place a single set of sheets between double-layer acrylic plates; place the acrylic plates holding the sheets horizontally and centered on the conveyor belt; pre-orient the acrylic plates along the conveyor belt through a strong magnetic field of upper S and lower N, wherein the strong magnetic field includes two upper and lower N52 NdFeB strong magnetic blocks, and the magnetism of the two N52 NdFeB strong magnetic blocks corresponds to a gradient distribution with strong edges and weak middle; a unidirectional magnetic field is formed in the middle; magnetization is performed for 200ms through a pulsed magnetic field with an intensity of 3.5T; after magnetization, the two magnetic sheets are reversed to realize a magnetized structure of mutual attraction, thereby obtaining the ultra-thin flexible magnetic eyelash magnetic sheet of this embodiment.
[0035] Example 5
[0036] The present embodiment provides an ultra-thin flexible magnetic eyelash magnet sheet, which is composed of samarium iron nitrogen magnetic powder, polypropylene resin, silane coupling agent, calcium stearate and zinc oxide raw materials; wherein the weight parts of the system formed by the samarium iron nitrogen magnetic powder and polypropylene resin and the amounts of other raw materials are specifically as follows.
[0037] SmFeN magnetic powder (from Example 1, average particle size 2 μm, coercivity Hc ≥ 12 kOe): 85wt%; Polypropylene (PP, melt index 20g / 10min): 15wt%; Silane coupling agent (KH-550): 1.5% of the mass of SmFeN magnetic powder; Calcium stearate: 0.3% of PP mass; Zinc oxide: 0.3% of PP mass.
[0038] The preparation process of the ultra-thin flexible magnetic eyelash magnet is as follows: Step 1: Mix the magnetic sheet raw materials according to proportion to obtain a mixed material; Step 2: putting the mixed materials into a twin-screw extruder, melt-blending and granulating at 200° C. to obtain pellets; Step 3: Place a layer of Teflon paper under the pressing fixture of the flat vulcanizer, then scatter the pellets, place another piece of Teflon paper on top of the pellets, and then press at 185°C. Control the pressing size to , pressing to a thickness of 0.14 mm to obtain a magnetic sheet precursor; Step 4: clean the burrs of the magnetic sheet precursor, cut it into two even sheets, stack them, and punch them into a single set of sheets using a sheet punching machine; Step 5, place a single set of sheets between double-layer acrylic plates; place the acrylic plates holding the sheets horizontally and centered on the conveyor belt; pre-orient the acrylic plates along the conveyor belt through a strong magnetic field of upper S and lower N, wherein the strong magnetic field includes two upper and lower N52 NdFeB strong magnetic blocks, and the magnetism of the two N52 NdFeB strong magnetic blocks corresponds to a gradient distribution with strong edges and weak middle; a unidirectional magnetic field is formed in the middle; magnetization is performed for 200ms through a pulsed magnetic field with an intensity of 3.5T; after magnetization, the two magnetic sheets are reversed to realize a magnetized structure of mutual attraction, thereby obtaining the ultra-thin flexible magnetic eyelash magnetic sheet of this embodiment.
[0039] Example 6
[0040] The present embodiment provides an ultra-thin flexible magnetic eyelash magnet sheet, which is composed of samarium iron nitrogen magnetic powder, polypropylene resin, silane coupling agent, calcium stearate and zinc oxide raw materials; wherein the weight parts of the system formed by the samarium iron nitrogen magnetic powder and polypropylene resin and the amounts of other raw materials are specifically as follows.
[0041] SmFeN magnetic powder (from Example 1, average particle size 2 μm, coercivity Hc ≥ 12 kOe): 89 wt%; Polypropylene (PP, melt index 20g / 10min): 11wt%; Silane coupling agent (KH-550): 1.5% of the mass of SmFeN magnetic powder; Calcium stearate: 0.3% of PP mass; Zinc oxide: 0.3% of PP mass.
[0042] The preparation process of the ultra-thin flexible magnetic eyelash magnet is as follows: Step 1: Mix the magnetic sheet raw materials according to proportion to obtain a mixed material; Step 2: putting the mixed materials into a twin-screw extruder, melt-blending and granulating at 200° C. to obtain pellets; Step 3: Place a layer of Teflon paper under the pressing fixture of the flat vulcanizer, then scatter the pellets, place another piece of Teflon paper on top of the pellets, and then press at 185°C. Control the pressing size to , pressing to a thickness of 0.14 mm to obtain a magnetic sheet precursor; Step 4: clean the burrs of the magnetic sheet precursor, cut it into two even sheets, stack them, and punch them into a single set of sheets using a sheet punching machine; Step 5, place a single set of sheets between double-layer acrylic plates; place the acrylic plates holding the sheets horizontally and centered on the conveyor belt; pre-orient the acrylic plates along the conveyor belt through a strong magnetic field of upper S and lower N, wherein the strong magnetic field includes two upper and lower N52 NdFeB strong magnetic blocks, and the magnetism of the two N52 NdFeB strong magnetic blocks corresponds to a gradient distribution with strong edges and weak middle; a unidirectional magnetic field is formed in the middle; magnetization is performed for 200ms through a pulsed magnetic field with an intensity of 3.5T; after magnetization, the two magnetic sheets are reversed to realize a magnetized structure of mutual attraction, thereby obtaining the ultra-thin flexible magnetic eyelash magnetic sheet of this embodiment.
[0043] Comparative Example 1 The present embodiment provides an ultra-thin flexible magnetic eyelash magnet sheet, which is composed of NdFeN magnetic powder, polypropylene resin, silane coupling agent, calcium stearate and zinc oxide raw materials; wherein, the weight parts of the system formed by NdFeN magnetic powder and polypropylene resin and the amounts of other raw materials are specifically as follows.
[0044] NdFeB magnetic powder: 87wt%; Polypropylene (PP, melt index 20 g / 10min): 13wt%; Silane coupling agent (KH-550): 1.5% of the mass of SmFeN magnetic powder; Calcium stearate: 0.3% of PP mass; Zinc oxide: 0.3% of PP mass.
[0045] The preparation process of the ultra-thin flexible magnetic eyelash magnet is as follows: Step 1: Mix the magnetic sheet raw materials according to proportion to obtain a mixed material; Step 2: putting the mixed materials into a twin-screw extruder, melt-blending and granulating at 200° C. to obtain pellets; Step 3: Place a layer of Teflon paper under the pressing fixture of the flat vulcanizer, then scatter the pellets, place another piece of Teflon paper on top of the pellets, and then press at 185°C. Control the pressing size to , pressing to a thickness of 0.14 mm to obtain a magnetic sheet precursor; Step 4: clean the burrs of the magnetic sheet precursor, cut it into two even sheets, stack them, and punch them into a single set of sheets using a sheet punching machine; Step 5, place a single set of sheets between double-layer acrylic plates; place the acrylic plates holding the sheets horizontally and centered on the conveyor belt; pre-orient the acrylic plates along the conveyor belt through a strong magnetic field of upper S and lower N, wherein the strong magnetic field includes two upper and lower N52 NdFeB strong magnetic blocks, and the magnetism of the two N52 NdFeB strong magnetic blocks corresponds to a gradient distribution with strong edges and weak middle; a unidirectional magnetic field is formed in the middle; magnetization is performed for 200ms through a pulsed magnetic field with an intensity of 3.5T; after magnetization, the two magnetic sheets are reversed to realize a magnetized structure of mutual attraction, thereby obtaining the ultra-thin flexible magnetic eyelash magnetic sheet of this embodiment.
[0046] Comparative Example 2 The present embodiment provides an ultra-thin flexible magnetic eyelash magnet sheet, which is composed of samarium iron nitrogen magnetic powder, polypropylene resin, silane coupling agent, calcium stearate and zinc oxide raw materials; wherein the weight parts of the system formed by the samarium iron nitrogen magnetic powder and polypropylene resin and the amounts of other raw materials are specifically as follows.
[0047] SmFeN magnetic powder (from Example 1, average particle size 2 μm, coercivity Hc ≥ 12 kOe): 87 wt%; Polypropylene (PP, melt index 20g / 10min): 13wt%; Silane coupling agent (KH-550): 1.5% of the mass of SmFeN magnetic powder; Calcium stearate: 0.3% of PP mass; Zinc oxide: 0.3% of PP mass.
[0048] The preparation process of the ultra-thin flexible magnetic eyelash magnet is as follows: Step 1: Mix the magnetic sheet raw materials according to proportion to obtain a mixed material; Step 2: putting the mixed materials into a twin-screw extruder, melt-blending and granulating at 200° C. to obtain pellets; Step 3: After the pellets are dried in a blast drying oven at 120°C for 7 hours, the pellets are calendered to produce rough sheets. The mold temperature is set to 120°C, the sheeting speed is 0.4m / min, and the sheet thickness is 0.5mm. The magnetic sheet is passed through three horizontal calenders, with the first two hot rollers at 100°C and the last cold roller at 10°C. The thickness of the magnetic sheet is adjusted accurately by 30% per pass to obtain a sheet with a thickness of 0.42mm. Step 4: clean the burrs of the magnetic sheet precursor, cut it into two even sheets, stack them, and punch them into a single set of sheets using a sheet punching machine; Step 5, place a single set of sheets between double-layer acrylic plates; place the acrylic plates holding the sheets horizontally and centered on the conveyor belt; pre-orient the acrylic plates along the conveyor belt through a strong magnetic field of upper S and lower N, wherein the strong magnetic field includes two upper and lower N52 NdFeB strong magnetic blocks, and the magnetism of the two N52 NdFeB strong magnetic blocks corresponds to a gradient distribution with strong edges and weak middle; a unidirectional magnetic field is formed in the middle; magnetization is performed for 200ms through a pulsed magnetic field with an intensity of 3.5T; after magnetization, the two magnetic sheets are reversed to realize a magnetized structure of mutual attraction, thereby obtaining the ultra-thin flexible magnetic eyelash magnetic sheet of this embodiment.
[0049] Comparative Example 3 The present embodiment provides an ultra-thin flexible magnetic eyelash magnet sheet, which is composed of samarium iron nitrogen magnetic powder, polypropylene resin, silane coupling agent, calcium stearate and zinc oxide raw materials; wherein the weight parts of the system formed by the samarium iron nitrogen magnetic powder and polypropylene resin and the amounts of other raw materials are specifically as follows.
[0050] SmFeN magnetic powder (from Example 1, average particle size 2 μm, coercivity Hc ≥ 12 kOe): 87 wt%; Polypropylene (PP, melt index 20g / 10min): 13wt%; Silane coupling agent (KH-550): 1.5% of the mass of SmFeN magnetic powder; Calcium stearate: 0.3% of PP mass; Zinc oxide: 0.3% of PP mass.
[0051] The preparation process of the ultra-thin flexible magnetic eyelash magnet is as follows: Step 1: Mix the magnetic sheet raw materials according to proportion to obtain a mixed material; Step 2: putting the mixed materials into a twin-screw extruder, melt-blending and granulating at 200° C. to obtain pellets; Step 3: Place a layer of Teflon paper under the pressing fixture of the flat vulcanizer, then scatter the pellets, place another piece of Teflon paper on top of the pellets, and then press at 185°C. Control the pressing size to , pressing to a thickness of 0.14 mm to obtain a magnetic sheet precursor; Step 4: clean the burrs of the magnetic sheet precursor, cut it into two even sheets, stack them, and punch them into a single set of sheets using a sheet punching machine; Step 5, place a single set of sheets between double-layer acrylic plates; place the acrylic plates holding the sheets horizontally and centered on the conveyor belt; pre-orient the acrylic plates along the conveyor belt through a strong magnetic field of upper S and lower N, wherein the strong magnetic field includes two upper and lower N52 NdFeB strong magnetic blocks, and the magnetism of the two N52 NdFeB strong magnetic blocks is evenly distributed; a unidirectional magnetic field is formed in the middle; magnetization is performed for 200ms using a pulsed magnetic field with an intensity of 3.5T; after magnetization, the two magnetic sheets are reversed to realize a magnetized structure of mutual attraction, thereby obtaining the ultra-thin flexible magnetic eyelash magnetic sheet of this embodiment.
[0052] Comparative Example 4 The present embodiment provides an ultra-thin flexible magnetic eyelash magnet sheet, which is composed of NdFeN magnetic powder, polypropylene resin, silane coupling agent, calcium stearate and zinc oxide raw materials; wherein, the weight parts of the system formed by NdFeN magnetic powder and polypropylene resin and the amounts of other raw materials are specifically as follows.
[0053] NdFeB magnetic powder: 87wt%; Polypropylene (PP, melt index 20 g / 10min): 13wt%; Silane coupling agent (KH-550): 1.5% of the mass of SmFeN magnetic powder; Calcium stearate: 0.3% of PP mass; Zinc oxide: 0.3% of PP mass.
[0054] The preparation process of the ultra-thin flexible magnetic eyelash magnet is as follows: Step 1: Mix the magnetic sheet raw materials according to proportion to obtain a mixed material; Step 2: putting the mixed materials into a twin-screw extruder, melt-blending and granulating at 200° C. to obtain pellets; Step 3: After the pellets are dried in a blast drying oven at 120°C for 7 hours, the pellets are calendered to produce rough sheets. The mold temperature is set to 120°C, the sheeting speed is 0.4m / min, and the sheet thickness is 0.5mm. The magnetic sheet is passed through three horizontal calenders, with the first two hot rollers at 100°C and the last cold roller at 10°C. The thickness of the magnetic sheet is adjusted accurately by 30% per pass to obtain a sheet with a thickness of 0.42mm. Step 4: clean the burrs of the magnetic sheet precursor, cut it into two even sheets, stack them, and punch them into a single set of sheets using a sheet punching machine; Step 5, place a single set of sheets between double-layer acrylic plates; place the acrylic plates holding the sheets horizontally and centered on the conveyor belt; pre-orient the acrylic plates along the conveyor belt through a strong magnetic field of upper S and lower N, wherein the strong magnetic field includes two upper and lower N52 NdFeB strong magnetic blocks, and the magnetism of the two N52 NdFeB strong magnetic blocks is evenly distributed; a unidirectional magnetic field is formed in the middle; magnetization is performed for 200ms using a pulsed magnetic field with an intensity of 3.5T; after magnetization, the two magnetic sheets are reversed to realize a magnetized structure of mutual attraction, thereby obtaining the ultra-thin flexible magnetic eyelash magnetic sheet of this embodiment.
[0055] The surface magnetic induction intensity of the flexible magnetic eyelash magnets prepared in Examples 2-6 and Comparative Examples 1-4 was tested by using a Gauss meter.
[0056] The test results are listed in Table 1. Table 1 is as follows: Table 1
[0057] By analyzing the data in Table 1, it can be learned that: compared with comparative examples 1-4, the magnetic induction intensity at the edge of the flexible magnetic eyelash magnetic sheet obtained in Examples 2-6 is greater than the magnetic induction intensity in the middle, and the distribution of the magnetic induction intensity increases evenly from the middle to the edge, and the magnetic induction intensity is at a moderate level. It will not be too high or too low to cause excessive suction to affect unloading or too little suction to easily fall off. The distribution of the magnetic induction intensity that increases evenly from the middle to the edge can also make the suction at the edge greater than the suction in the middle, thereby making the wearing effect more curled and natural, and the burden on the eyelashes is lighter and more comfortable.
[0058] The basic physical properties of the flexible magnetic eyelash magnets prepared in Examples 2-6 and Comparative Examples 1-4 were tested, including the thickness of the magnets, the number of bending resistances, and the folding phenomenon. The testing method was as follows: Magnetic sheet thickness: using digital display vernier caliper; Bending resistance: refer to standard GB / T 457-2008.
[0059] Folding phenomenon: Place the magnetic sheet in a 25°C constant temperature chamber for 48 hours, then take it out, fold it 180°, and observe it visually.
[0060] The test results are listed in Table 2, which is as follows: Table 2
[0061] By analyzing the data in Table 2, it can be found that: compared with Comparative Examples 1-2 and Comparative Example 4, the thickness of the flexible magnetic eyelash magnets of Examples 2-6 is between 0.14-0.24 mm, the number of bending resistance is greater than 500, and there is no crack on the fold, which shows that the flexible magnetic eyelash magnets prepared by the method of using samarium iron nitrogen magnetic powder as the raw material and gradient distributed directional magnetization in the present invention are thinner and have better folding resistance.
[0062] The corrosion resistance of the flexible magnetic eyelash magnets prepared in Examples 2-6 and Comparative Examples 1-4 was tested by a salt spray test under the following conditions: Salt spray test: reference standard GB / T 10125-2021; Test conditions: neutral salt spray test (NSS); Salt spray test chamber: temperature control accuracy ±1°C, spray volume 1.0-2.0 mL / 80cm² / h; Salt solution: 5wt% NaCl solution, pH 6.5-7.2 (25℃).
[0063] The test results are listed in Table 3, which is as follows: Table 3
[0064] By analyzing the data in Table 3, it can be found that: compared with Comparative Examples 1 and 4, the surface changes of the flexible magnetic eyelash magnets of Examples 2-6 are smaller within the same test time, which indicates that the use of samarium iron nitrogen magnetic powder as a raw material in the present invention makes the flexible magnetic eyelash magnets have stronger corrosion resistance.
[0065] The magnetic performance attenuation rate of the flexible magnetic eyelash magnets prepared in Examples 2-6 and Comparative Examples 1-4 was tested after the salt spray test. The testing method was as follows: testing the surface magnetic induction of the magnets after the salt spray test, and calculating the surface magnetic induction of the magnets before the salt spray test using a formula.
[0066] The calculation results are listed in Table 4, which is as follows: Table 4
[0067] By analyzing the data in Table 4, it can be found that compared with Comparative Examples 2-3, the flexible magnetic eyelash magnet of Example 2-6 has a lower magnetic attenuation rate within the same time, which indicates that the use of samarium iron nitrogen magnetic powder as a raw material can make the magnetic retention effect of the flexible magnetic eyelash magnet better.
[0068] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. An ultra-thin flexible magnetic eyelash magnet, characterized in that: Each set of eyelash magnets consists of two upper and lower magnets, on which opposite magnetic poles are arranged respectively, and the magnetism of the opposite magnetic poles is distributed in a gradient manner on the magnets, with strong magnetism at the edges and weak magnetism in the middle. The magnetic sheet comprises the following raw materials in parts by weight: 85-89 parts of samarium iron nitrogen magnetic powder and 11-15 parts of polypropylene.
2. The ultra-thin flexible magnetic eyelash magnet according to claim 1, characterized in that: The magnetic sheet also includes the following raw materials: silane coupling agent, calcium stearate, zinc oxide; Wherein, the weight of the silane coupling agent is 1.5% of the samarium iron nitrogen magnetic powder; the weight of the calcium stearate is 0.3% of the polypropylene; and the weight of the zinc oxide is 0.3% of the polypropylene.
3. The ultra-thin flexible magnetic eyelash magnet according to claim 1, characterized in that: The SmFeN magnetic powder is subjected to surface corrosion resistance treatment, and the surface corrosion resistance treatment method is: adding phosphoric acid and corrosion inhibitor to the SmFeN magnetic powder and stirring evenly to form a mixed system, and then reacting at 100° C. for 6 hours.
4. The ultra-thin flexible magnetic eyelash magnet according to claim 3, characterized in that: The phosphoric acid is used in an amount of 1 wt % of the mixed system, and the corrosion inhibitor is used in an amount of 1 wt % of the mixed system.
5. The ultra-thin flexible magnetic eyelash magnet according to claim 1, characterized in that: The thickness of the magnetic sheet is 0.14-0.24 mm.
6. The ultra-thin flexible magnetic eyelash magnet according to claim 1, characterized in that: The surface magnetic induction intensity of the magnetic sheet is 30-50 mT.
7. The ultra-thin flexible magnetic eyelash magnet according to claim 1, characterized in that: The surface magnetic induction intensity at the edge of the magnetic sheet is greater than the surface magnetic induction intensity at the center, and the surface magnetic induction intensity at the edge of the magnetic sheet is 38-50mT, and the surface magnetic induction intensity at the center of the magnetic sheet is 30-42mT.
8. The ultra-thin flexible magnetic eyelash magnet according to claim 7, characterized in that: The surface magnetic induction intensity increases uniformly from the center position of the magnetic sheet to the edge of the magnetic sheet.
9. The method for preparing the ultra-thin flexible magnetic eyelash magnet according to any one of claims 1 to 8, characterized in that: The steps include: Step 1: Mix the magnetic sheet raw materials according to proportion to obtain a mixed material; Step 2: putting the mixed materials into a twin-screw extruder, melt-blending and granulating at 180-210° C. to obtain pellets; Step 3: Place a layer of Teflon paper under the pressing fixture of the flat vulcanizer, then scatter the pellets, place another piece of Teflon paper on top of the pellets, and then press at 185°C. Control the pressing size to , pressing to a thickness of 0.14-0.24 mm to obtain a magnetic sheet precursor; Step 4: clean the burrs of the magnetic sheet precursor, cut it into two even sheets, stack them, and punch them into a single set of sheets using a sheet punching machine; Step 5: Perform gradient distributed directional magnetization on each group of sheets to form a counter-attractive magnetized structure.
10. The method for preparing the ultra-thin flexible magnetic eyelash magnet according to claim 9, characterized in that: In step 5, the method of performing gradient distributed directional magnetic punching on each group of sheets includes the following steps: Step a: Place a single set of sheets between double layers of acrylic plates; Step b, placing the plate holding the sheet material horizontally and centered on the conveyor belt; Step c, pre-orienting the plate with a conveyor belt through a strong magnetic field of upper S and lower N, wherein the strong magnetic field includes two upper and lower N52 NdFeB strong magnetic blocks, and the magnetism of the two N52 NdFeB strong magnetic blocks is in a gradient distribution with strong edges and weak middle; a unidirectional magnetic field is formed in the middle; Step d, magnetizing by a pulsed magnetic field; Step e: After magnetization, the two magnetic sheets are reversed to realize a counter-attractive magnetization structure.
11. The method for preparing the ultra-thin flexible magnetic eyelash magnet according to claim 10, characterized in that: In step d, the intensity of the pulsed magnetic field is 3.5 T, and the magnetization time is 200 ms.
Citation Information
Patent Citations
Moulding stamper for magnetic shoe of permanent magnet DC motor stator and using method thereof
CN101741186A
Ultrathin flexible magnetic sheet and application
CN113363047A
Method for producing phosphate-coated SmFeN-based anisotropic magnetic powder, and bonded magnet
CN116685424A
Eyelash ornament, wearing clip and eyelash ornament manufacturing method
CN118923989A
Preparation method of rare-earth bonding magnet
CN1808648A
Cited By
Ultrathin strong magnetic sheet, preparation method thereof and application of ultrathin strong magnetic sheet in eyelash ornament
CN120954845A
An ultrathin strong magnetic sheet, a preparation method thereof and application thereof in a mascara
CN120954845B